Application of the single blood sample method to estimate feline glomerular filtration rate in a clinically relevant situation. Issue 12 (December 2013) - Katayama, Masaaki; Sasaki, Asuka; Takayasu, Mariko; Shimamura, Shunsuke; Uzuka, Yuji; Murayama, Isao; Satoh, Hiroshi; Furuhama, Kazuhisa
To compare glomerular filtration rate (GFR) estimated by a single blood sample method, the non-ionic contrast medium iodixanol (40 mg I/kg) and the standard GFR tracer inulin (50 mg/kg) were co-administered as a bolus intravenous injection to 12 cats, followed by blood collection 60 and 90 mins later. Serum iodixanol and inulin concentrations were measured separately by high-performance liquid chromatography and colourimetric assay. A correlation ( r = 0.90, P <0.01) was noted between GFR values estimated by the single-blood-sample method using iodixanol and inulin, indicating that this procedure can apply to feline GFR estimates, even if different GFR tracers are used. In a feline kidney transplantation study, the GFR was monitored subsequently by this simplified iodixanol method throughout a 750-day observation period with no adverse reactions. The results demonstrate that the simplified method, including the volume of distribution, can be used as an alternative or expedient tool in a clinically relevant situation.